In Vitro Platelet Binding Compared with In Vivo Thrombus Imaging Using αIIbβ3-Targeted Radioligands - Knight, Linda C.; Romano, Jan E.; Maurer, Alan H. (Thrombosis and Haemostasis, 1998)
Radioligands for the αIIbβ3 integrin on platelets are being studied for their ability to image venous thrombi and pulmonary emboli. One such radioligand, 123I-bitistatin, was previously shown to have higher thrombotic uptake in an animal model than other disintegrins, but the reason for this difference was not clear. The purpose of this study was to evaluate three labeled disintegrins, bitistatin, kistrin and barbourin, to look for in vitro differences in platelet binding which could explain the in vivo behavior.Disintegrins labeled with 125I were compared in vitro for extent of binding to platelets and rates of binding and dissociation. These findings were related to organ distribution and image quality for imaging thrombotic lesions, following administration of 123I-disintegrins in an animal model. Fibrinogen at 8.8 μmol/l was able to displace 125Ibarbourin and 125I-kistrin more rapidly from ADP-stimulated platelets, with half-times of 3.5 and 10.7 min, compared with 125I-bitistatin (31.6 min). At equivalent concentrations in whole blood, a higher percentage of bitistatin bound to platelets compared with the other two. In vivo, kistrin and barbourin had significantly lower thrombus:muscle and pulmonary embolus:lung ratios in images compared with bitistatin. There was evidence of more metabolic deiodination of labeled kistrin and barbourin in vivo compared with bitistatin. A surprising finding was that conventional in vitro platelet binding studies did not predict the relative in vivo behavior of labeled disintegrins.The results suggest that labeled bitistatin has improved targeting of thrombi because it is less easily displaced from stimulated platelets, permitting longer lesion retention. It also appears to have a greater association with resting platelets in the blood, which may increase bioavailability and delay metabolic breakdown.